Analysis Role of Digital Marketing and Self Image Improving Student Self Presentation in Batam Using Instagram - Muhammad Ardiansyah (Universitas Medan Area, 2020)
Nowadays Students often use social media as a tool to communicate and search for a lot of information, social media can also influence changes in the self-image of students shared on social media. This study aims to determine the large social media users of Instagram among students, to analyze Instagram social media as a tool used by students in self-development and self-image, to know the importance of digital marketing in shaping student self-image, analyzing the development of students' Self Presentations, knowing how large students in showing self-image using Instagram social media, knowing the importance of Self Presentation within the university. This study uses variables namely digital marketing, and Self Image as independent variables, Self Presentation as the dependent variable. The target respondents of this study were all university students in the city of Batam by using a sample of 392 students. This research concluded that self image plays a role in shaping student self-appearance because students try to look neat and attractive when uploading videos on Instagram Stories about themselves, wanting to look good in photos or videos, so users can display a good image and other Instagram users who see can give good comments as well.Keywords: Social Media, Instagram, Digital Marketing, Self Image, Self Presentation.